The Influence Of Work Discipline, Nurses' Therapeutic Communication And Service Quality On Patient Satisfaction At Mitra Clinic - Ellin Herlina; Cindy Woelandari; Bambang Sumardi; Hartanto Halim (International Journal of Management, Economic, Business and Accounting, 2024)
Purpose of the study — To find out how much influence Work Discipline, Nurse Therapeutic Communication and Service Quality partially or simultaneously have on Patient Satisfaction at Mitra Sehat Clinic CirebonResearch method—provide This research design uses a quantitative approach with a survey method and this type of research is causal associative research with data analysis techniques using multiple linear regression analysis. The research location was the Mitra Sehat Cirebon Clinic with a population of patients who came to the Mitra Sehat Cirebon Clinic over a period of 6 days from 11-16 September 2023. The sample size was calculated using the Slovin formula, resulting in a sample of 92 people.research method that you employResult— 1) There is a partial positive and significant influence of Work Discipline on Patient Satisfaction at the Cirebon Mitra Sehat Clinic, amounting to 62%. 2) There is a partial positive and significant influence of Nurse Therapeutic Communication on Patient Satisfaction at the Cirebon Mitra Sehat Clinic, amounting to 13.5%. 3) There is a partial positive and significant influence of Service Quality on Patient Satisfaction at the Cirebon Mitra Sehat Clinic of 22.6%. 4) There is a simultaneous positive and significant influence of Work Discipline, Nurse Therapeutic Communication and Service Quality on Satisfaction at the Cirebon Mitra Sehat Clinic amounting to 88.5% while the remaining 11.5% is influenced by other factors.Conclusion— It is important to note that while work discipline, nurse therapeutic communication, and service quality were found to have a significant impact on patient satisfaction, there may still be other factors not accounted for in this study that influence patient satisfaction. Further research could explore additional variables and their contributions to patient satisfaction in healthcare settings.